A standardized methanol extract of Eclipta prostrata (L.) L. (Asteraceae) reduces bronchial hyperresponsiveness and production of Th2 cytokines in a murine model of asthma. (23rd February 2017) - Morel, Lucas Junqueira de Freitas; Azevedo, Bruna Cestari de; Carmona, Fábio; Contini, Silvia Helena Taleb; Teles, Aristônio Magalhães; Ramalho, Fernando Silva; Bertoni, Bianca Waléria; França, Suzelei de Castro; Borges, Marcos de Carvalho; Pereira, Ana Maria Soares
Abstract: Ethnopharmacological relevance: Eclipta prostrata (L.) L. (Asteraceae) has been used in Brazilian traditional medicine to treat asthma and other respiratory illnesses. Aims of the study: To investigate the effects of different doses of a standardized extract of E. prostrata using a murine model of allergen induced asthma. Materials and methods: Balb/c mice were sensitized twice with ovalbumin (OVA) administered intraperitoneally and challenged over four alternate days with nasal instillations of OVA solution. The standardized methanol extract of E. prostrata was administered in doses of 100, 250 and 500 mg kg − 1 concomitantly with nasal instillation over seven consecutive days. Control animals were treated with dexamethasone or saline solution. Bronchial hyperresponsiveness, production of Th1 and Th2 cytokines, allergen sensitization, airway and lung inflammation, mucous secretion and airway remodeling were assessed. Results: The concentrations of chemical markers in the standardized methanol extract were 0.02% oroboside, 1.69% demethylwedelolactone and 1.71% wedelolactone. Treatment with 250 mg kg −1 of extract, which provided 0.745, 4.22 and 4.30 mg kg − 1 day −1 of oroboside, demethylwedelolactone and wedelolactone, respectively, significantly reduced ( P <0.05) respiratory resistance and elastance. Such effects were comparable with those produced by dexamethasone. The total number of inflammatory cells and eosinophils in the bronchoalveolar lavage and the concentrations of interleukin (IL)-4, IL-5 and IL-13 in lung homogenate were significantly reduced ( P <0.05) by the methanol extract of E. prostrata. Conclusion: The results presented herein demonstrate for the first time the anti-inflammatory activity of E. prostrata in a murine model of asthma, thereby supporting the ethnopharmacological uses of the plant. Graphical abstract: